QUALITY OF ADMINISTRATIVE SERVICE POPULATION IN IMPROVING PUBLIC SERVICES BASED ON KEPMEN NO. 25 OF 2004 - A. Ariadi (P3M Stia Al Gazali Barru and Meraja media, 2021)
This study aims to determine the quality of population administration services in terms of issuing Identity Cards in Lalolang Village based on the Decree of the Minister of Administrative Reform No. Kep/25/M.PAN/2/2004 dated February 24, 2004 concerning General Guidelines for Compiling the Community Satisfaction Index for Government Service Units. , and the factors that affect the quality of service for issuing Identity Cards in Lubtik Pakam III Sub-district, Lalolang District based on the Ministerial Decree No. 25 of 2004. This study uses a qualitative descriptive method with a case study approach with inductive data analysis techniques using a single table and then looking for the average service quality variable average. Collecting data using library research and field research. The population is the people of Lalolang Village totaling 4,656 people and the number is determined as a sample of 150 people from 9 (nine) neighborhoods, sampling using simple random sampling technique. Based on the results of data analysis, it is known that. The quality of population administration services in terms of issuing Resident Identity Cards in Lalolang Village based on the Decree of the Minister of Administrative Reform No. Kep/25/M.PAN/2/2004 dated February 24, 2004 concerning General Guidelines for Compiling the Community Satisfaction Index for Service Units of Government Agencies is included in the poor category . where from the 14 elements of service, there are 7 (seven) elements of service that are not good and 7 (seven) elements of service that are included in the good category, namely courtesy and friendliness of officers, certainty of service schedules, environmental comfort. Based on the results of the research and the conclusions mentioned above, the authors contribute suggestions to improve aspects of knowledge where the real aspect is one of the requirements for improving the quality of human resources so that they can create human resources who are able to think ahead.